Perovskitas de SrSnO3:Fe depositadas sobre suportes Comerciais para redução de no com CO - Santos, Guilherme Leocárdio Lucena dos (2013)
Strontium stannate, SrSnO3, is a perovskite wile orthorhombic structure which has interesting dielectric properties, besides several technological applications such as catalysis of nitrogen oxides. In this work, SrSnO3, SrSn0,9Fe0,1O3-x and Sr0,9Sn0,9Fe0,1O3-x were obtained by the polymeric precursor method using metallic tin as precursor (Sn0) and were deposited on commercial catalytic supports (CeO2, TiO2, -Al2O3 and ZrO2) for application as catalysts in the reaction of reduction of NO with CO. The catalysts were characterized by thermogravimetric analysis (TG / DTA), Xray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), infrared spectroscopy (IR), Raman spectroscopy, analysis of the surface area by the BET method and scanning electron microscopy with field emission (FE-SEM). The catalytic tests were conducted in a reactor with gas mixture containing stoichiometric quantities of nitrogen monoxide (NO) and carbon monoxide (CO), in helium, in the temperature range from 300 °C to 700 °C. The XRD results showed that the perovskite had a high long-range order, and low amount of secondary phase (SrCO3). The IR spectra confirmed these data by presenting a reduction of vibration bands related to carbonates groups. The Raman spectra and the calculation of the inclination angles among the octahedra indicated a short range disorder. The deposition of perovskite on the supports presented good dispersion. The catalytic tests showed that the perovskite doped with iron showed the best percentage of conversion of NO and CO. The perovskite deposited on the ZrO2 showed the best catalytic conversion.